Peranan Guru Pendidikan Agama Buddha Dalam Meningkatkan Sila Pertama Pancasila Buddhis Pada Peserta Didik Kelas VII Di SMP Maitreyawira Palembang - Hendra Saputra; Rida Jelita; Hosan Hosan (STAB Maitreyawira, 2023)
The knowledge about the Five Principles of Buddhism is the life foundation of every Buddhist generally and students specifically. Therefore, this research aims to improve the application of the first principle of the Five Principles of Buddhism among the seventh grade students at SMP Maitreyawira Palembang. In this research, the descriptive qualitative method is used. This method intensively learns the background of the current situation, and the environmental interaction according to the social units comprising: individuals, groups, institutions or society. Based on the data analysis, it was found that the role of a teacher as a motivator can motivate and help the students build a strong will and hope so that their life style can abide by the first principle. Besides, the role of a teacher as an inspirer using learning media can inspire the students to apply the first principle of the Five Principles of Buddhism. It is hoped that his research has a contribution for both teachers and students in practicing the Five Principles of Buddhism, especially the first principle, and for enriching the study of Buddha Dharma in Indonesia.